PREVENTING PREJUDICE: A GUIDE FOR COUNSELLORS AND EDUCATORS (Authors: Joseph G. Ponterotto & Paul B. Pederson) - Smith, David C. (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 1994)
Joseph G. Ponterotto & Paul B. Pederson. PREVENTING PREJUDICE: A GUIDE FOR COUNSELLORS AND EDUCATORS. Newbury Park, CA: Sage Publications (1993). 184 pp. $29.95 c1oth; $14.95 paper. ISBN 0-8039-5284-8.